Changes in corneal structure with continuous wear of High-Dk Soft contact lenses: a pilot study - González-Méijome, José Manuel (2003)
Despite numerous studies that have considered the effects of extended wear of high-Dk soft contact lenses on ocular physiology, little attention has been paid to the impact of such lenses on central or peripheral corneal thickness and curvature. The present study aims to report the time course of changes in corneal thickness and curvature that accompanies the 30-night continuous wear of new silicone hydrogel soft contact lenses in a neophyte population in a longitudinal study. Methods. Six subjects wore high-Dk lotrafilcon (Dk = 140) on a 30-night replacement schedule for 12 months. Only measurements from the right eye were considered for analysis. Topographical measurements of corneal thickness and curvature were taken. The same parameters were monitored for an additional period of 3 months after lens removal. Results. An almost homogenous increase in corneal radius of curvature was detected for all the locations studied, being statistically significant for the 4-mm cord diameter area. This effect was associated with a progressive thinning effect for the central cornea, whereas midperipheral and peripheral areas did not display such a thinning effect during continuous wear. These effects were still evident for the central cornea 3 months after contact lens wear discontinuation. Conclusions. Continuous wear of high-Dk silicone hydrogel contact lenses is associated with clinically appreciable changes in topographical corneal curvature, whereas only a reduction in corneal thickness is appreciated in the central area. This effect seems to be a result of mechanical pressure induced by these hybrid hyperpermeable materials, characterized by a higher modulus of elasticity. The small sample size compromises the conclusions addressed from this study, and further work will be necessary to confirm the present results.